Praxeologias adotadas no ensino de Matemática na perspectiva da educação inclusiva em Aracaju - Matos, Anthoniberg Carvalho de (2018)
The present research is bound to studies academic master's degree in teaching of natural sciences and Mathematics by the Universidade Federal de Sergipe-UFS and aims, analyze the influence of teacher training on the teachers ' practice in math education for deaf students included in regular elementary schools and adult education-ADULT and YOUTH EDUCATION. The central question of research – As the praxeologias adopted by math teachers to teach deaf students are influenced by the processes of your teacher education? -branched out in other issues were defined in order to include the dimension of education by means of the following conceptual categories: Deaf Education (STROBEL, 2008; GESSER, 2009; SACKS, 2015; Souza, 2010; SHARMA, SKILIAR, 2012 and 2013), Deaf Education and mathematics education (BORGES, 2006; GIL, 2007; BIRTH, 2009; PASSION, 2010; Souza, 2013 and 2016 sea), public policy from existing legislation and official documents; and Praxeologias (CHEVALLARD, 1996 e SOUZA, 2015). Adopted as main subjects of research, Math teachers of a school in the State network in Aracaju (SE), meet as many deaf people included, in addition to work in different types of elementary school (regular and EJA). So, this is a research with qualitative approach of exploratory and descriptive-explanatory, whose analysis of the phenomenon and of the content of the subjects was conducted through a questionnaire and observation of lessons. The questionnaire was applied to two math teachers working with deaf students, in which the issues touch on personal aspects and of the training process, apart from their respective views on the subject of research. On observation of the praxis of these teachers, it was possible to see a gap of knowledge/training on appropriate methodologies to teach deaf students, a factor that may interfere directly in the educational process. There was also a diversity of inclusion in a same class, putting the teacher in constant challenges to their praxeológicas organizations; interpreters confusing your paper, leaving the deaf students without access to which is explained by the teacher. Finally, as a result of these phenomena that institucionalizam the everyday Math lessons for deaf students, the use of inadequate praxeologias without a pedagogical interaction between teacher-student-interpreter.